A Review of Language, Executive Function, and Intervention in Autism Spectrum Disorder - Friedman, Laura; Sterling, Audra (Seminars in Speech and Language, 2019)
Difficulties with both executive functions and language skills are common but variable in autism spectrum disorder (ASD). Executive functions and language skills are related to one another, such that vocabulary, syntax, and pragmatics are related to domains of working memory, shifting, and inhibition in ASD, although the directionality of these relationships remains unclear. Moreover, interventions that target pragmatic ability have been found to improve executive function skills, and conversely, executive function interventions are linked with improvements in social skills in children with ASD. We review the literature on executive functions, language skills, and their relationship in ASD; discuss factors that may be driving inconsistent findings; and explore clinical applications from the research thus far.
Keywords: autism spectrum disorder; executive function; language; intervention